Chronological Order of Appearance of Extraintestinal Manifestations Relative to the Time of IBD Diagnosis in the Swiss Inflammatory Bowel Disease Cohort. Issue 8 (August 2015) - Vavricka, Stephan R.; Rogler, Gerhard; Gantenbein, Claudine; Spoerri, Muriel; Prinz Vavricka, Mareike; Navarini, Alexander A.; French, Lars E.; Safroneeva, Ekaterina; Fournier, Nicolas; Straumann, Alex; Froehlich, Florian; Fried, Michael; et al.
Abstract : Background: Data evaluating the chronological order of appearance of extraintestinal manifestations (EIMs) relative to the time of inflammatory bowel disease (IBD) diagnosis is currently lacking. We aimed to assess the type, frequency, and chronological order of appearance of EIMs in patients with IBD. Methods: Data from the Swiss Inflammatory Bowel Disease Cohort Study were analyzed. Results: The data on 1249 patients were analyzed (49.8% female, median age: 40 [interquartile range, 30–51 yr], 735 [58.8%] with Crohn's disease, 483 [38.7%] with ulcerative colitis, and 31 [2.5%] with indeterminate colitis). A total of 366 patients presented with EIMs (29.3%). Of those, 63.4% presented with 1, 26.5% with 2, 4.9% with 3, 2.5% with 4, and 2.7% with 5 EIMs during their lifetime. Patients presented with the following diseases as first EIMs: peripheral arthritis 70.0%, aphthous stomatitis 21.6%, axial arthropathy/ankylosing spondylitis 16.4%, uveitis 13.7%, erythema nodosum 12.6%, primary sclerosing cholangitis 6.6%, pyoderma gangrenosum 4.9%, and psoriasis 2.7%. In 25.8% of cases, patients presented with their first EIM before IBD was diagnosed (median time 5 mo before IBD diagnosis: range, 0–25 mo), and in 74.2% of cases, the first EIM manifested itself after IBD diagnosis (median: 92 mo; range, 29–183 mo). Conclusions: In one quarter of patients with IBD, EIMs appeared before the time of IBD diagnosis. Occurrence of EIMs should prompt physicians to look for potential underlying IBD. Abstract : Article first published online 27 May 2015Supplemental Digital Content is Available in the Text.